2016
DOI: 10.18632/oncotarget.12648
|View full text |Cite
|
Sign up to set email alerts
|

INPP5D rs35349669 polymorphism with late-onset Alzheimer's disease: A replication study and meta-analysis

Abstract: Inositol polyphosphate-5-phosphatase (INPP5D) was reported to be associated with Alzheimer's disease (AD) through modulating the inflammatory process and immune response. A recent genome-wide association study discovered a new locus single nucleotide polymorphism (SNP, rs35349669) of INPP5D which was significantly associated with susceptibility to late-onset Alzheimer's disease (LOAD) in Caucasians. In this study, we investigated the relations between the INPP5D polymorphism rs35349669 and LOAD in Han Chinese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Although genetic variants in INPP5D have been associated with LOAD risk [5,6,20,21], the role of INPP5D in AD remains unclear. We identified that INPP5D expression levels are increased in the brain of LOAD patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although genetic variants in INPP5D have been associated with LOAD risk [5,6,20,21], the role of INPP5D in AD remains unclear. We identified that INPP5D expression levels are increased in the brain of LOAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Recent large-scale genome-wide association studies (GWAS) reported that many genetic loci associated with LOAD risk are related to inflammatory pathways, suggesting that microglia are involved in modulating AD pathogenesis [3,4]. Among the microglia-related genetic factors in LOAD, a common variant in INPP5D (phosphatidylinositol 3,4,5-trisphosphate 5-phosphatase 1), rs35349669, confers an increase in LOAD risk (OR=1.08) [4,5]. Conversely, the intronic INPP5D variant rs61068452 is associated with a reduced CSF t-tau/Aβ1-42 ratio, plays a protective role in LOAD (p=1.48E-07) [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Spleen tyrosine kinase (SYK) has been shown to play a role in AD pathological lesions, and SYK was therefore considered as a potential drug target for AD 22 . Phosphatidylinositol 3,4,5trisphosphate 5-phosphatase 1 (INPP5D), identified as one of the genetic risk factors for LOAD 23 , affects AD pathology by regulating microglia 24 . Inhibiting tyrosine-protein kinase (HCK) has proved to disturb microglia function and exacerbate neuropathology and neuroinflammation 25 .…”
Section: Discovery Of Disease-associated Microglia Specific Molecularmentioning
confidence: 99%